The pastoral epistles : the Greek text with introduction and commentary - Simpson, E.K., (Edmund Kidley). (London, UK : Tyndale, 1954)
Includes bibliographical references and indexes
Includes bibliographical references.
Keywords: Bible. -- commentaries